Messaggio secondario e vocalità nello Jakob von Gunten di Fabio Condemi - Masi, Silvia (Kritik. Rivista di letteratura e critica culturale, 2024)
This essay proposes to reconstruct, in the footsteps of phonostylist Iván Fónagy, the secondary message in the Walserian Jakob von Gunten and investigate the ways in which it is represented in the theatrical “remediation”, taking on the vocal gesture as a metaphor for a drive reality. Signed by Fabio Condemi and presented at the Venice Theatre Biennale in 2018, the adaptation declines, in the pluricodic composition of the stage event, the harrowing drama of a deliberately emptied existence told by Walser’s irreverent style, founded on labyrinthine chatter and uninterrupted irony.